Prácticas socioecológicas y estrategias de resiliencia comunitaria para una agricultura sostenible en el Bajo Sinú, Colombia (2023)
This research examines the socioecological practices of rural communities as an epistemological foundation to configure community resilience strategies and face socio-environmental conflicts due to limited access to water, loss of biodiversity and ancestral knowledge. To meet this objective, a qualitative approach was used with a non-experimental transectional research design of exploratory type with a case study method in the Association of Producers for Community Development of the Cienaga del Bajo Sinú-Asprocig, Colombia. As a main result, it is argued that the rural communities of the lower Sinú organized in associations carry out self-management models that promote the articulation of social and ecological systems, socio-environmental sustainability and make an adequate management of use and access to ecosystem services. Copyright © FrancoAngeli This work is released under Creative Commons Attribution - Non-Commercial - No Derivatives License. For terms and conditions of usage please see: https://creativecommons.org.